The physiological relationship between the Nano-organic fertilizer Optimus plus and growth and yield of wheat (Ibaa 99) - AL-SAIDAN KHUDHAIR JOUDAH YASIR (University of Thi-Qar Journal of agricultural research, 2024)
To face the challenges of wheat crop production using modern technologies and to raise the rate of the production unit produced by using nanoparticles (Optimus plus fertilizer), know the focus, and choose its best spray date, which can improve the growth and total yield, a potting experiment was carried out during the agricultural season 2023-2024 using design RCBD by three replications. The amounts of nano-organic fertilizer were one of the primary factors (C) (1 (C1), 2 (C2), 3 (C3)) ml. L-1, while The application of the nano-organic fertilizer was the second component (S) at the plant growth stages (Seedling (S1), Tillering (S2), Anthesis (S3)). The study’s findings demonstrated significant physiological relationship of the amounts (C3) and the spray stage (S2) to wheat’s development and yield (Ibaa 99), giving them the highest averages for most of the studied traits. The concentration (C3) supplied the greatest averages (plant height, chlorophyll content, flag leaf area, number of tillers, total grain yield) (104.67cm, 0.7544, 55.99cm2, 429.0 tiller.m-2, 8.171ton.ha-1) respectively, while concentration (C1) gave the highest average weight of 1000 grains amounting to 45.81 g. Spraying stage (S2) was superior in the studied of the most traits (they were not significantly different from the spraying stage (S3)) (109.00 cm, 0.7656, 59.40 cm2, 412.0 tiller.m-2, 44.71 - 44.70 g, 7.911 - 7.502 ton.ha-1), respectively, spraying stage (S1) produced the most grains per spike, which didn’t much change from the spraying stage (S2) (67.1 - 66.0) grain.spike-1. Interaction treatment (C3S2) excelled in giving it the highest average grain yield of 8.847, which was superior to the total grain yield of the study agents individually, which confirms the importance of the physiological relationship of nanoparticles (Optimus plus fertilizer) for the wheat growth and yield.